Optimization of the Two-Wheel Patrol of Samapta Units to Prevent the Crime of Motor Vehicle Theft in the Jurisdiction of the Sukoharjo Police - Saputra, Muh. Fahreza (Advances in Police Science Research Journal, 2024)
This study aimed to identify and describe the management system and organizational resources of the Samapta Unit of the Sukoharjo Police in carrying out two-wheeled patrols to prevent criminal acts of theft in the jurisdiction of the Sukoharjo Police. This is based on the number of cases of motor vehicle theft that often occur throughout 2022. To reveal problems with the management system and organizational resources of the Sukoharjo Police Samapta Unit in carrying out patrols, this study uses POAC management theory and 6M theory, as well as optimization and patrol concepts by utilizing a qualitative analytical descriptive method with a retrospective case study. Based on the results of observations, interviews, and document studies conducted in this study, it was concluded that so far the implementation of the two-wheeled patrol of the Sukoharjo Police Samapta Unit in terms of its management system and organizational resources has not been optimal. Therefore, optimizing the implementation of the Samapta Unit’s two-wheeled patrols to prevent criminal acts of theft in the jurisdiction of the Sukoharjo Police should be guided by Perkabaharkam Polri Number 1 of 2017 concerning Patrols. In terms of the management system, the role of the highest office holder is needed in monitoring the performance of patrols at every stage from preparation to supervision. Especially in the preparation of activity plans from the goals, methods, and patterns that are carried out, it is necessary to be more innovative so that the implementation is always in line with developments in the conditions of Kamtibmas in the community environment. In terms of organizational resources, the Sukoharjo Police Samapta Unit needs to increase the quantity and improve the quality of personnel, make a budget plan that is able to meet all the needs and requirements of carrying out two-wheeled patrols, maintain the condition of existing infrastructure, create more innovative two-wheeled patrol implementation methods, and in its implementation target to apply selective priority in preventing criminal acts of theft.